Bevacizumab Revisited: Its Use in Different Mouse Models of Ocular Pathologies. (May 2015) - Hollanders, Karolien; Van Bergen, Tine; Van de Velde, Sarah; Sijnave, Davine; Vandewalle, Evelien; Moons, Lieve; Stalmans, Ingeborg
ABSTRACT Purpose: Previous reports have yielded conflicting data on the activity of bevacizumab (Avastin), a recombinant humanized monoclonal antibody against VEGF-A, in the mouse. The current study was designed to further explore the use of this VEGF inhibitor in various murine models of ocular diseases and compare it to the widely used murine anti-VEGF-R2 neutralizing antibody (DC101). Methods: Murine models of laser-induced choroidal neovascularization (CNV), oxygen-induced retinopathy (OIR) and glaucoma filtration surgery (GFS) were used to investigate the effect of bevacizumab. Mice either received an intravitreal (CNV–OIR) or subconjunctival (GFS) injection. In all models, they were divided in two groups (n = 10 per group). In the first group, one eye was injected with bevacizumab (1 µl; 25 µg) and the other eye was used as a negative control and received an injection of NaCl (1 µl; 0.9%). In the second group, one eye was injected with DC101 (1 µl; 6.2 µg), whereas an isotype-matched control antibody (1C8; 4.8 µg) was administered in the contralateral eye. Treatment outcome was studied by clinical investigation (GFS) and immunohistological analysis of angiogenesis (CD31/FITC-dextran/H&E) and fibrosis (Sirius Red). Results: Analysis of blood vessel density (CNV) and blood vessel growth (OIR) showed a comparable decrease after intravitreal administration of bevacizumab or DC101. Furthermore, in the mouse model of GFS, clinical investigation of the bleb and a CD31 staining on sections demonstrated that subconjunctival injection of both antibodies similarly improved the surgical outcome (bleb area and survival) by reducing angiogenesis. Moreover, morphometric analysis after Sirius Red staining showed a comparable reduction in collagen deposition after administration of the inhibitors. Conclusion: Our findings consistently demonstrate that bevacizumab is as effective as the murine anti-VEGF-R2 antibody (DC101) in mouse models of CNV, OIR and GFS, thus confirming its suitability for translational ophthalmological research.